Identification of Wool and Cashmere Fibers by Preparation of Hollow-like Carbon Tubes after Carbonization. Issue 16 (28th November 2022) - Tang, Wenyang; Fu, Chiyu; Xia, Liangjun; Lyu, Pei; Bai, Wenli; Chen, Wu; Xu, Weilin
ABSTRACT: Identification of wool and cashmere has attracted considerable attention in various research fields due to the outstanding properties of fibers. Herein, the hollow-like carbon tubes were facilely prepared by carbonization using the waste wool fibers, which were further characterized by elemental analysis and scanning electron microscope (SEM). After carbonization, hollow-like structures were observed in wool, while cashmere still presented in solid shapes at cross-sectional morphologies. Furthermore, the medulla existed in wool can be pyrolyzed after the carbonization process, which may be an effective way to distinguish the cashmere from wool by their obvious differences in fiber shapes, fiber sizes and residual weights. The effects of temperature on the properties of wool and cashmere were also analyzed. The proportions of hollow wool tubes increased with the rise of temperature, reaching more than 90% at 500°C. Apart from that, the mean diameter of treated wool (16.022 μm) was larger than treated cashmere (8.399 μm), which both shrunk nearly 50% than pristine fibers, and the residual weight of cashmere (68.95%) was higher than wool (62.98%). This method could be extended for identifying specialty fibers like fine yak fiber and yak hair, paving the way for distinguishing protein fibers in multiple areas.